Morphological variability and genetic marker stability of 16 monoclonal pennate diatom strains under medium-term culture. Issue 4 (2nd October 2022) - Mohamad, Heba; Mora, Demetrio; Skibbe, Oliver; Abarca, Nélida; Deutschmeyer, Verena; Enke, Neela; Kusber, Wolf-Henning; Zimmermann, Jonas; Jahn, Regine
Abstract : Monoclonal diatom strains are the basis for integrative taxonomical studies combining molecular and morphological data for better taxonomic resolution and identification. The identification of diatoms, based on morphological features of the frustule, is difficult due to the variability of characters within and amongst species. The longer the cultivation time, the more cell size is reduced during asexual reproduction. Many divisions of the cell complicate identification as morphological characters of the frustule change at different rates in different taxa and teratologies can develop. Morphological variability raises the question whether the investigated genetic markers are stable over the cultivation time span. Sixteen monoclonal pennate diatom strains, identified as 10 different species in six genera, were cultivated for up to 18 or 24 months. It was shown that molecular data for the 18S-V4, rbc L, and psb A markers were stable for the entire cultivation time of all taxa. Images of the valves of the strains were taken every six months and examined morphometrically. Depending on the time since the start of the cultures, the morphological features showed high variability, particularly in length and shape, whereas width and number of striae, costae or fibulae were more stable, depending on the taxon and strain. A limited time span and good culture conditions seem to be prerequisite to avoid the production of teratological frustules. The results of parallel cultures in a unique experimental design are compared to observations from the literature dealing with single strains or special cognitive interests.